Functional Outcomes of Thoracolumbar Junction Spine Fractures - Wall, Bradford A.; Moskowitz, Alan; Whitaker, M. Camden; Jones, Teresa L.; Stuckey, Ryan M.; Carr-Maben, Catherine L.; Chong, Alexander CM. (Kansas Journal of Medicine, 2019)
Introduction. Few studies have evaluated the functionaloutcomes of traumatic thoracic and lumbar vertebral bodyfractures. This study evaluated the functional and clinicaloutcomes of patients, who sustained a fracture to thethoracolumbar area of the spine (T10 to L2 region), with≥ 25° kyphosis versus those with less kyphotic curvature.Methods. The trauma registry records of two level 1 traumacenters using ICD-9 codes for fracture to the thoracolumbarjuncture (T10 to L2 region) were reviewed. Kyphosis anglewas measured on the standing lateral thoracolumbar (T1 -L5) radiograph at initial trauma and at clinical follow-up.Functional outcome questionnaires, including the OswestryDisability Questionnaire (ODQ), the Roland Morris DisabilityQuestionnaire (RMDQ), and the Nottingham Health Profile(NHP), were evaluated at clinical follow-up. Work statusand medication used after trauma also were recorded.Results. A total of 38 patients met the inclusive criteria. Seventeenpatients (45%) had ≥ 25° kyphosis and 21 patients (55%)had < 25° kyphosis at follow-up. These two groups were similarbased on sex and age. Based on the ODQ Score, the RMDQScore, and the NHP, no statistically significant differenceswere detected between the two groups in regards to energy,pain, mobility, emotional reaction, social isolation, and sleep.Conclusions. Patients who sustained a fracture to the thoracolumbararea of the spine with ≥ 25° kyphosis do notreport worse clinical outcomes. When using the kyphosisangle as an indication for surgery, it should be used withcaution and not exclusively. KS J Med 2017;10(2):30-34.